Distal Pancreatectomy Fistula Risk Score (D-FRS): Development and International Validation. Issue 5 (7th May 2023) - De Pastena, Matteo; van Bodegraven, Eduard A.; Mungroop, Timothy H.; Vissers, Frederique L.; Jones, Leia R.; Marchegiani, Giovanni; Balduzzi, Alberto; Klompmaker, Sjors; Paiella, Salvatore; Tavakoli Rad, Shazad; Groot Koerkamp, Bas; van Eijck, Casper; et al.
Abstract : Objective: To develop 2 distinct preoperative and intraoperative risk scores to predict postoperative pancreatic fistula (POPF) after distal pancreatectomy (DP) to improve preventive and mitigation strategies, respectively. Background: POPF remains the most common complication after DP. Despite several known risk factors, an adequate risk model has not been developed yet. Methods: Two prediction risk scores were designed using data of patients undergoing DP in 2 Italian centers (2014–2016) utilizing multivariable logistic regression. The preoperative score (calculated before surgery) aims to facilitate preventive strategies and the intraoperative score (calculated at the end of surgery) aims to facilitate mitigation strategies. Internal validation was achieved using bootstrapping. These data were pooled with data from 5 centers from the United States and the Netherlands (2007–2016) to assess discrimination and calibration in an internal-external validation procedure. Results: Overall, 1336 patients after DP were included, of whom 291 (22%) developed POPF. The preoperative distal fistula risk score (preoperative D-FRS) included 2 variables: pancreatic neck thickness [odds ratio: 1.14; 95% confidence interval (CI): 1.11–1.17 per mm increase] and pancreatic duct diameter (OR: 1.46; 95% CI: 1.32–1.65 per mm increase). The model performed well with an area under the receiver operating characteristic curve of 0.83 (95% CI: 0.78–0.88) and 0.73 (95% CI: 0.70–0.76) upon internal-external validation. Three risk groups were identified: low risk (<10%), intermediate risk (10%–25%), and high risk (>25%) for POPF with 238 (18%), 684 (51%), and 414 (31%) patients, respectively. The intraoperative risk score (intraoperative D-FRS) added body mass index, pancreatic texture, and operative time as variables with an area under the receiver operating characteristic curve of 0.80 (95% CI: 0.74–0.85). Conclusions: The preoperative and the intraoperative D-FRS are the first validated risk scores for POPF after DP and are readily available at: http://www.pancreascalculator.com . The 3 distinct risk groups allow for personalized treatment and benchmarking.